Does mass closure of midline laparotomies stand the test of time? A random control clinical trial. - Ausobsky, J. R. (Royal College of Surgeons of England, 1985)
We compared the incidence of wound failure (burst abdomen and incisional herniation up to 4 years after operation) in a consecutive series of 282 major laparotomies closed with continuous monofilament nylon, and randomly allocated to mass (all layers except skin) or layered (anterior and posterior aponeuroses separately sutured) techniques. Surgeons were free to choose the site and direction of incision which resulted in a preponderance of midline incisions in the mass, and of paramedian incisions in the layered, group. One patient in the former, and two in the latter, burst their abdomens during early convalescence, and 17 incisional hernias were discovered within four years in the mass group compared with four in the layered group (log rank X2 7.16, P less than 0.01). Seven hernias in the former, and one in the latter, group were not detected within eight months of operation. We conclude that layered closure of a paramedian incision results in a lower incidence of incisional hernias than mass closure of a midline incision and that many hernias are not discovered until years after operation.